BMI and plasma lipid levels with risk of proliferative diabetic retinopathy: a univariable and multivariable Mendelian randomization study - Shu, Yiyang; Zhou, Qi; Shao, Yuting; Lin, Hui; Qu, Shen; Han, Wenting; Lv, Xiao; Bi, Yanlong (Frontiers in Nutrition, 2023)
The aim of the study was to determine whether causal effect exists between body mass index (BMI) or plasma lipid levels and proliferative diabetic retinopathy (PDR) risk in humans.We utilized univariable (UVMR) and multivariable two-sample mendelian randomization (MVMR) analyses to confirm the effects of BMI and plasma lipid levels on the risk of PDR. Genetic variants associated with BMI and three plasma lipids were obtained from GWAS summary datasets generated by many different consortia and were deposited in the MR-Base database. The GWAS summary data for PDR from the FinnGen biobank included 212,889 participants of European ancestry (8,681 cases and 204,208 controls). Inverse variance weighted (IVW) was applied as the main MR analysis. Sensitivity analysis was used to evaluate the robustness of our findings.In the UVMR analysis, the causal associations of genetically predicted BMI with PDR presented a positive association (OR = 1.120, 95% CI = 1.076-1.167, P < 0.001), and the lower HDL-C level was associated with a higher risk of PDR (OR= 0.898, 95% CI = 0.811-0.995, P =0.040). No evidence of an association between LDL-C or TG levels (P>0.05) and PDR risk was found. In the MVMR analysis controlling for HDL-C level, there was strong evidence for a direct causal effect of BMI on the risk of PDR (OR = 1.106, 95%CI=1.049, 1.166, P<0.001, IVW). After adjusting for BMI, there was no evidence for a direct causal effect of HDL-C level on the risk of the PDR (OR = 0.911, 95% CI= 0.823, 1.008, P= 0.072). Sensitivity analyses confirmed that the results were reliable and stable.Robust evidence was demonstrated for an independent, causal effect of BMI in increasing the risk of PDR. Further work is required to understand the potential biological mechanisms underlying this causal relationship.